2022
DOI: 10.1002/cl2.1268
|View full text |Cite
|
Sign up to set email alerts
|

Mental disorder, psychological problems and terrorist behaviour: A systematic review and meta‐analysis

Abstract: Background: The link between mental health difficulties and terrorist behaviour has been the subject of debate for the last 50 years. Studies that report prevalence rates of mental health difficulties in terrorist samples or compare rates for those involved and not involved in terrorism, can inform this debate and the work of those responsible for countering violent extremism.Objectives: To synthesise the prevalence rates of mental health difficulties in terrorist samples (Objective 1-Prevalence) and prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 314 publications
(392 reference statements)
2
13
0
1
Order By: Relevance
“…Research by Spaaij [23] too, noted the frequent occurrence of psychological disturbance among lone actors, although this observation was based on a small sample. In contrast, a recent Campbell Systematic Review and meta‐analysis involving 73 different samples and 13,648 terror subjects [29] reported a life‐time prevalence rate of 17.4% for mental disorder and a pooled prevalence rate of 25.5% for studies reporting psychological problems and suspected disorder. In conclusion, the authors reported that, “this review does not support the assertion that terrorist samples are characterised by higher rates of mental health difficulties than would be expected in the general population (p. 2).”…”
Section: Discussionmentioning
confidence: 95%
“…Research by Spaaij [23] too, noted the frequent occurrence of psychological disturbance among lone actors, although this observation was based on a small sample. In contrast, a recent Campbell Systematic Review and meta‐analysis involving 73 different samples and 13,648 terror subjects [29] reported a life‐time prevalence rate of 17.4% for mental disorder and a pooled prevalence rate of 25.5% for studies reporting psychological problems and suspected disorder. In conclusion, the authors reported that, “this review does not support the assertion that terrorist samples are characterised by higher rates of mental health difficulties than would be expected in the general population (p. 2).”…”
Section: Discussionmentioning
confidence: 95%
“…We are also reminded of two selection effects: one in which people with more socially oriented personalities seek the company of like‐minded individuals, and the other where (extremist) groups are likely to deny (continued) membership to individuals perceived as unreliable or erratic, whether as a result of limited social skills or mental health–related issues (Lindekilde et al., 2019). Arguably, such selection effects are part of the reason why mental health issues may be particularly prevalent among lone‐actor terrorists and less so group‐based ones (Sarma et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Whether mental health issues are associated with involvement in terrorism has long been subject to debate (Gill, Clemmow, et al., 2021). Recent meta‐analytical work finds that, excepting particular subpopulations (e.g., lone actors), those involved in terrorist violence exhibit unremarkable rates of diagnosed disorder or suspected disorder (Sarma et al., 2022). We contributed to this subject by collecting clinical information on the presence or absence of neurodevelopmental and mental health disorders, before and during radicalization.…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…Existing literature has explored the origins of terrorism, delving into their sociological and psychological aspects to gain a deeper understanding of the primary factors influencing their actions (Hudson, 1999). These studies had examined on the causality of terrorism whether in aspects of mental disorder, youth psychological vulnerabilities, immigration and various other factors that comes into such reasoning of their actions (Harpviken, 2020;Light and Thomas, 2021;Sarma et al, 2022). This is where the criminal justice systems are required to play their role in ensuring that such actions are penalised and offenders would not repeat such offences.…”
Section: Criminal Justicementioning
confidence: 99%